(untitled) (Western European Journal of Medicine and Medical Science, 2024)
Hepatorenal syndrome (HRS) is a serious consequence of advanced liver disease that causes kidney failure. The purpose of this study is to assess the clinical, pathogenetic, and genetic factors that influence the development and prognosis of hepatorenal syndrome in the Khorezm region of Uzbekistan. A retrospective research of 50 patients diagnosed with HRS at regional hospitals investigated the role of genetic predisposition, pathogenetic processes, and clinical markers. The findings indicate a strong link between specific genetic markers, pathogenetic variables, and clinical outcomes, which could enhance the prognosis and care of patients with hepatorenal syndrome in the region.